Low-power current-mode resistive readout circuit using 0.13µm technology for biomedical MEMS applications / Jamilah Karim - Karim, Jamilah (UiTM Press, 2025)
This paper presents an innovative current-mode interface circuit design specifically for resistive readout circuits. The main goal is to create and evaluate resistive readout circuits utilizing a current-mode architecture. The design and simulation of the resistive readout circuit are conducted using Silterra's 0.13µm technology, powered by a 1.2V supply voltage, with the aid of Cadence ADE. This architecture is optimized for low power consumption, drawing only 15µW, while maintaining high sensitivity for resistive values ranging from 500KΩ to 199MΩ. The circuit's output voltage varies between 0.48V and 1.03V, allowing for precise measurement and analysis of resistive sensor data.